2016
DOI: 10.1016/j.theriogenology.2016.05.041
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different regimens of estradiol benzoate treatments followed by long-acting progesterone to prepare noncycling mares as embryo recipients

Abstract: The present study evaluated the influence of different regimens of estradiol benzoate (EB) treatments followed by a single dose of long-acting progesterone (LA P4) on plasma estrogen and P4 concentrations in noncyclic mares prepared as embryo recipients. Twenty-one anestrous mares were distributed into three groups (n = 7 mares per group), according to the EB dose received (single dose of 2.5 mg, total of 5 mg in decreasing doses, and total of 10 mg in decreasing doses), which was followed by a single administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 18 publications
1
5
0
1
Order By: Relevance
“…In the present experiment, the higher P4 level was found on D1 after treatment, reaching mean values of 15 ng/mL, and decreased gradually thereafter. The plasma P4 profile from day D0 until D5 after LA P4 treatment is in agreement with previous results described in non-cyclic mares also treated with 1.5 g of LA P4 [25,28,29].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present experiment, the higher P4 level was found on D1 after treatment, reaching mean values of 15 ng/mL, and decreased gradually thereafter. The plasma P4 profile from day D0 until D5 after LA P4 treatment is in agreement with previous results described in non-cyclic mares also treated with 1.5 g of LA P4 [25,28,29].…”
Section: Discussionsupporting
confidence: 92%
“…The dose of 1.5 g of LA P4 was considered effective in terms of reaching the minimum concentrations required (2.5 ng/mL [23]) for pregnancy establishment and maintenance [24,25] until day five after its administration. However, P4 profiles were different between cyclic and non-cyclic P4 treated mares.…”
Section: Discussionmentioning
confidence: 99%
“…In the past few years, various doses of E2 has been given to intact non-cyclic recipient mares and after observation of uterine edema, long acting progesterone (LA P4) [6,7] or altrenogest [2,9] has been administered three to eight days prior to embryo transfer. Recently, it was demonstrated that the administration of a single dose of 2.5 mg of estradiol benzoate to anestrous mares produces similar estrogen concentration to that found in cyclic mares [10]. Moreover, it is known that plasma P4 concentration after injection of 1500 mg of LA P4 at seven day intervals is compatible with P4 concentrations found in cyclic mares during the luteal phase (>4 ng/mL) [11].…”
Section: Introductionmentioning
confidence: 88%
“…It is an estradiol analog commonly used in livestock for inducing weight gain and synchronising estrus cycles in heifers and cattle. 6,7 However, as an analogue of EDC, E2B binds with estrogen receptors (ERs) which are expressed in human cells such as breast, bone and prostate, leading to relevant metastatic tumour formation. 8,9 As early as 1988, the use of this kind of xenobiotic agent for improving the growth and feed conversion rates of food-producing animals has been banned in the European Union (EU) and no residues of these anabolic substances should be present in animal products.…”
Section: Introductionmentioning
confidence: 99%